(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article offers an original classification procedure based on Mamdani fuzzy inference system (FIS) dedicated to compute multiple criterions each from different type of psychological profiles. The modelling and information analysis of the FIS are developed to draw a general conclusion from several psychological criterions in order to provide better pre-course lecturer preparation and thus better students’ perception. Simulation experiments are carried out in MATLAB environment.